Combining NMR Spectroscopy and Molecular Dynamic Simulations to Solve and Analyze the Structure of Protein-RNA Complexes - Campagne, Sebastien; Krepl, Miroslav; Sponer, Jiri; Allain, Frederic H-T (Methods in enzymology, 2019)
Understanding the RNA binding specificity of protein is of primary interest to decipher their function in the cell. Here, we review the methodology used to solve the structures of protein-RNA complexes using solution-state NMR spectroscopy: from sample preparation to structure calculation procedures. We also describe how molecular dynamics simulations can help providing additional information on the role of key amino acid side chains and of water molecules in protein-RNA recognition.
Keywords: CELF Proteins; Molecular Dynamics Simulation; interakční proteinové domény a motivy; vodíková vazba; Protein Conformation, beta-Strand; Protein Interaction Domains and Motifs; vazebná místa; RNA Splicing Factors; vazba proteinů; CELF proteiny; lidé; simulace molekulární dynamiky; Nucleic Acid Conformation; RNA; sestřihové faktory; konformace nukleové kyseliny; magnetická rezonanční spektroskopie; konformace proteinů, beta-řetězec; Hydrogen Bonding; Thermodynamics; Protein Conformation, alpha-Helical; Magnetic Resonance Spectroscopy; termodynamika; Protein Binding; konformace proteinů, alfa-helix; Binding Sites; Humans